Kepemimpinan Berbasis Karakter: Studi Kasus Proses Pengambilan Keputusan Kepala Sekolah TK An Nur Malang - Mutiara Fahrunisa; Muhammad Al Fatih; Laela Lutfiana Rachmah; Zainul Arifin; Alfarobi Ahmad Sulaiman (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
The purpose of this study was to examine how character-based leadership influences the principal’s decisions at An Nur Kindergarten in Malang and how these decisions affect the quality of early childhood education. To collect data, this study used a qualitative case study design. In-depth interviews with the principal and teachers, direct observation of learning and managerial activities at the school, and documentation of school policies and programs were conducted. Data were analyzed through stages of reduction, presentation, and thematic analysis. The results indicate that the principal’s character-based leadership is reflected in a participatory, responsive decision-making process oriented toward moral principles such as honesty, empathy, and responsibility. This decision-making process improves learning quality, creates an inclusive educational environment, and strengthens a school culture that supports children’s social and emotional development. The results indicate that character-based leadership plays a strategic role in the principal's decisions at an early childhood education institution. Furthermore, this leadership is a crucial component in improving the quality of early childhood education.